Love, Be a Poem. The Rhetoric of Seduction in the Love Poetry of Vesna Parun - Vuković, Tvrtko (Poznańskie Studia Slawistyczne, 2023)
In the broadest sense, the paper is a discussion of Vesna Parun’s love poetry. The basic idea is that, on the one hand, it adheres to the romantic understanding of literature as a representation of the deepest personal feelings, universal truths, and essential values and, on the other hand, that it acts as a confirmation that the experience of love is fundamentally literary, and that literature is a form of unbridled love for linguistic seduction. For this reason, the author’s love poetry is not approached as a representation of her private life, love feelings, or relationships, but as a complex relationship between figurative language and a romanticized idea of love. In other words, it is interpreted as a discourse or rhetorical event that simultaneously constructs and deconstructs concepts such as authentic experience, sincere sensitivity, primordial love, or stable identity, and provides an opportunity to raise important ethical and political questions in the face of its ambivalence.